2021
DOI: 10.1002/1873-3468.14030
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic PINK1 orchestrates protein translation during proteasomal stress by phosphorylating the translation elongation factor eEF1A1

Abstract: Mutations in PINK1 (PTEN-induced putative kinase 1) are associated with autosomal recessive early-onset Parkinson's disease. Full-length PINK1 (PINK1-l) has been extensively studied in mitophagy; however, the functions of the short form of PINK1 (PINK1-s) remain poorly understood. Here, we report that PINK1-s is recruited to ribosome fractions after short-term inhibition of proteasomes. The expression of PINK1-s greatly inhibits protein synthesis even without proteasomal stress. Mechanistically, PINK1-s phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This gene encodes eEF1A1, one of the most abundant proteins in the cell, which is involved in the elongation phase of protein synthesis, facilitating the delivery of aminoacyl-tRNAs to the ribosome (30). However, eEF1A1 is not only a translation factor, but also exhibits chaperone-like activity and participates in cellular responses to various stresses, including heat-shock, proteasomal stress, and ER stress (30)(31)(32). Moreover, eEF1A1 has been reported to inhibit Gcn2-mediated eIF2α phosphorylation; thus, its decreased expression could also positively regulate ATF4 signaling (30).…”
Section: Pathway Explorer Analysismentioning
confidence: 99%
“…This gene encodes eEF1A1, one of the most abundant proteins in the cell, which is involved in the elongation phase of protein synthesis, facilitating the delivery of aminoacyl-tRNAs to the ribosome (30). However, eEF1A1 is not only a translation factor, but also exhibits chaperone-like activity and participates in cellular responses to various stresses, including heat-shock, proteasomal stress, and ER stress (30)(31)(32). Moreover, eEF1A1 has been reported to inhibit Gcn2-mediated eIF2α phosphorylation; thus, its decreased expression could also positively regulate ATF4 signaling (30).…”
Section: Pathway Explorer Analysismentioning
confidence: 99%
“…PINK1 is translated in the cytoplasm and transported across the outer mitochondrial membrane (OMM) and the inner mitochondrial membrane (IMM), where it is cleaved by mitochondrial processing peptidase (MPP) and presenilin-associated rhomboid-like protease (PARL), and subsequently returned to the cytoplasm where, under normal conditions, it is either degraded by the proteasome or stabilized by a chaperone protein, exerting an inhibitory effect on mitophagy through interactions with Parkin (an ubiquitin E3 ligase that mono-ubiquitinates and poly-ubiquitinates proteins) and protein kinase A (PKA) [ 145 ]. There is also evidence that cytosolic PINK1 acts as a sensor of the UPS stress as its accumulation upon proteasome inhibition results in the PINK1-dependent phosphorylation of the translation elongation factor, known as the eukaryotic translation elongation factor 1 alpha 1 (eEF1A1), leading to decreased translational activity [ 146 ]. Upon mitochondrial damage or dysfunction, the mitochondrial membrane potential is decreased, causing PINK1 to remain on the OMM where it is dimerized and becomes phosphorylated [ 147 ].…”
Section: Molecular Components In the Intersections Of Ups And Autopha...mentioning
confidence: 99%
“…Due to PINK1's ability to rapidly accumulate on the OMM and activate in response to mitochondrial stressors, it has been suggested that PINK1 functions as a sensor to probe for damaged mitochondria [ 31 , 32 ]. Recently, it was also reported that PINK1-s (a short form of PINK1), as a sensor of proteasomal activities, protected cells against proteasome stress through inhibiting protein synthesis [ 33 , 34 ]. Subsequent homodimerization of PINK1 on the OMM leads to autophosphorylation, which promotes kinase activation and facilitates the translocation of Parkin to the membrane of damaged mitochondria and recruitment of substrates ubiquitin to the mitochondria [ 13 , 27 , 35 ].…”
Section: Mitophagymentioning
confidence: 99%